Pengaruh Lingkungan Kerja, Stres Kerjaan Work Family Conflict Terhadap Kinerja Pegawai Puskesmas Prigen Kabupaten Pasuruan - Ruliyanti, Linda Fuji; Djaelani, Abdul Kodir; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to identify how much influence the work environment, work stress, and work family conflict have on employee performance (case study of Prigen Health Center). Sampling using saturated sampling technique and the results obtained 45 respondents. Data obtained by distributing questionnaires to employees of the Prigen Health Center. Data analysis in this study using SPSS. Data testing techniques used in this study include validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis test, f test, t test and multiple determination coefficient test (R2). The results of this study indicate that the work environment and work family conflict have no effect on employee performance. While work stress has a positive and significant effect on employee performance. Keywords: Effect of Work Environment, Work Stress, and Work Family Confilct on Employee Performance